EUt+ Pedagogical Framework - Parmaxi, Antigoni; Kakoulli-Constantinou, Elis; Christou, Eirini; Pasia, Marina (My University, 2025)
The EUt+ Pedagogical Framework establishes a comprehensive, evidence-based approach to higher education that responds to the evolving demands of the 21st century global economy and the changing landscape of learning. Following an agile iterative design process using the Successive Approximation Model (SAM), this framework provides both a pedagogical foundation and practical guidance for transformative education in technology, engineering, and design fields. This framework establishes a common pedagogical terminology and approach across the EUT+ alliance while allowing for local adaptation and innovation, ultimately contributing to the advancement of a dynamic and inclusive learning environment across and beyond the EUT+ alliance